Family-Based Early Intervention to Improve Motor Development of Child with Cerebral Palsy - Soemarna, Paula Amelia Hany; Rochyadi, Endang; Susetyo, Budi; Muchlisah, Anugerah (Angstrom Centre of Education, 2023)
This research is motivated by the lack of understanding of families, especially parents, on child development, in this study the development that will be discussed is motor development in children with cerebral palsy who have quite complex developmental delays. The purpose of this study is to increase the family's understanding of the development of children according to their age which is expected by parents to be able to intervene independently, therefore an early intervention program with family resources is needed for children with cerebral palsy. The method used in this study is a descriptive method with a qualitative approach using observation and interviews to explore data and objective conditions of the family.